O uso de linguagem documentária em catálogos coletivos de bibliotecas universitárias: um estudo de avaliação sociocognitiva com protocolo verbal - Boccato, Vera Regina Casari [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (Escola de Ciência da Informação da UFMG, 2010)
Avaliou-se o uso de linguagem documentária alfabética de catálogos coletivos, na perspectiva das bibliotecas universitárias e no contexto sociocognitivo dos indexadores e dos usuários. Concluiu-se que o uso adequado de linguagens documentárias de áreas científicas especializadas faz-se por meio da avaliação quanto à atualização, especificidade e compatibilidade para atender às necessidades de indexação e recuperação da informação.

We have realized an evaluation study of the alphabetic indexing language use of the online collective catalogs in the perspective of the university libraries and in the socio-cognitive context of indexers and users. of the university libraries. We have concluded that the adequate use of indexing languages of specialized scientific areas becomes by means of evaluation as to updating, specificity and compatibility in order to meet the needs of indexing and information retrieval.
The use of indexing language in collective catalogs of university libraries: a study of socio-cognitive evaluation with verbal protocol
Keywords: Linguagem Documentária; Avaliação; Metodologia qualitativa sociocognitiva; Catálogos públicos de acesso online; Bibliotecas universitárias; Protocolo verbal; Indexing language; Evaluation; Qualitative-socio-cognitive methodology; Public catalogs of online access; University libraries; Verbal Protocol